Realization of Radar Illusion Using Active Devices. (23rd October 2012) - Cao, B. Z.; Sun, L.; Mei, Z. L.
Abstract : A new method is proposed for realizing radar illusion of an electromagnetic target by using active devices. The devices are installed around the target but may closely cover the target or not, leading to closed or open configurations. The amplitudes and phases of the active devices are determined by using T-matrix method. The numerical computation is calculated using MATLAB, and the results show that this method is convenient, flexible, and efficient, which has important significances for implementation of novel electromagnetic devices.